ABOUT THE SEMANTICS OF FRENCH WINGED EXPRESSIONS RELATING TO SACRED TEXTS (Scientific journal of the Fergana State University, 2024)
Winged expressions have their own position and place as a separate linguistic unit; they are distinguished by such qualities as stability, meaningfulness, separate design, active use, associations with an event or phenomenon, reproducibility in the mind, belonging to a specific author or source. The sources of origin of French catchphrases are different, among which sacred texts occupy a special place. These popular expressions are rich in content and essence. They can figuratively describe a person’s character, situation, interpersonal relationships, as well as various contradictions, natural and social phenomena observed in life, starting from the birth of a person. The following article discusses the semantics of the winged expressions of the sacred texts.